A Novel Directive, Dispersion-Free UWB Radiator with Superb EM-Characteristics for Multiband/Multifunction Radar Applications - Tran, D.; Haider, N.; Aubry, P.; Szilagyi, A.; Lager, I.E.; Yarovoy, A.; Ligthart, L.P. (IntechOpen, 2011)
None